2016
DOI: 10.1590/s0080-623420160000500004
|View full text |Cite
|
Sign up to set email alerts
|

Association between secondhand smoking in the home and respiratory morbidity in preschool children

Abstract: Objective: Identifying the prevalence of secondhand smoking in the home and its association with morbidity and hospitalization from respiratory causes in preschool children. Method: This is a cross-sectional study conducted in five early childhood education centers at a public university in São Paulo. Sample size calculation was performed and the participants were randomly determined. Data were collected through questionnaires completed by family members or caregivers of 215 children. Chi-square and Student's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
1
0
7
Order By: Relevance
“…Regarding smoker mothers, there was a 4% higher prevalence of allergic rhinitis, corroborating the studies that confirm passive smoking as a triggering factor for chronic and respiratory diseases, with children being the most affected, as they spend more time exposed to fumes, especially when the mother or caregiver are the ones who smoke 20,30 . A study confirmed that maternal smoking was the strongest of all the associated features for allergic rhinitis, rhinoconjunctivitis, and eczema, especially in the 6-7 years age group 20 .…”
Section: Discussionsupporting
confidence: 82%
“…Regarding smoker mothers, there was a 4% higher prevalence of allergic rhinitis, corroborating the studies that confirm passive smoking as a triggering factor for chronic and respiratory diseases, with children being the most affected, as they spend more time exposed to fumes, especially when the mother or caregiver are the ones who smoke 20,30 . A study confirmed that maternal smoking was the strongest of all the associated features for allergic rhinitis, rhinoconjunctivitis, and eczema, especially in the 6-7 years age group 20 .…”
Section: Discussionsupporting
confidence: 82%
“…Em estudo conduzido por Jorge et al ( 2016) tem-se explícito que a exposição passiva ao tabagismo apresenta associação com dificuldades de aprendizagem nas crianças, e que ter pais fumantes leva a maiores ocorrências de dificuldades de aprendizagem, problemas de comportamento e a dificuldades de linguagem na criança. Sigaud, Castanheira & Costa (2016) verificaram associação entre tabagismo passivo em crianças em domicílio com risco aumentado de apresentar sintomas respiratórios, como respiração rápida e retração subdiafragmática, bem como morbidades respiratórias relacionadas a doenças no ouvido. Fica evidente que possuir nível de escolaridade elevado constitui fator protetivo, todavia, verifica-se desconhecimento por parte dos pais e/ou responsáveis quanto aos danos de ter um fumante na família.…”
Section: Discussionunclassified
“…The population of young humans is also more exposed to nicotine through passive smoking, especially in the domestic environment (Nazar et al, 2014;Yousuf et al, 2020), as well as being more vulnerable to the harm caused by inhaling tobacco smoke (Tucker et al, 2019). Some reasons for this include their immunological immaturity, narrow and short airways, and long periods indoors, such as at home (Öberg et al, 2011;Sigaud et al, 2016). In addition, babies and children inhale twice the amount of household dust compared to adults, and thus inhale more cigarette smoke (Thomson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%